THE ROLE OF CYP3A4*1B POLYMORPHISM IN THE DEVELOPMENT OF PHARMACORESISTANTEPILEPSY IN UZBEK POPULATION - Tuychibaeva, Nodira; Alimkhodzhaeva, Parakhat; Boboev, Kodirjon; Bekhzod, Ibadov (International Journal of Psychosocial Rehabilitation, 2020)
Depending on the assessment method, data on the prevalence of epilepsy may vary, however, this neurological disorder is considered one of the most common. [1]. With appropriate treatment with antiepileptic drugs, about 60-70% of patients can be relieved of seizures, however, despite the progress made in the treatment of epilepsy and the emergence of the latest antiepileptic drugs, from 30 to 40% of patients are pharmacoresistant[2,3,4]. Pharmacoresistant epilepsy is defined as the inability to achieve a stable remission of seizures when using two well-tolerated and correctly selected antiepileptic drugs (in mono- or polytherapy mode) [5]. In addition to relapsing seizures, patients with drug-resistant epilepsy often experience psychosocial problems, an increased risk of injury, and a risk of sudden unexpected death (SUDEP) [4,6].